Associations among Discharge Opioid Prescribing and Inpatient Postpartum Opioid Usage after Delivery - Veade, Ashley (AJP Rep, 2020)
Objective  The aim of the study is to identify an association between inpatient opioid consumption and prescription at discharge after vaginal delivery (VD) and cesarean delivery (CD). Methods  This retrospective cohort study included women with an active inpatient opioid order after VD or CD between July and October of 2018 at a single academic tertiary hospital. Women with opioid use disorder, 3rd or 4th degree lacerations, wound complications, and peripartum hysterectomy were excluded. Oxycodone 5-mg (mg) tablets consumed postpartum and prescribed at discharge and sociodemographics were recorded. Primary outcome was the number of oxycodone 5-mg tablets prescribed at discharge. Outcomes were analyzed using multivariable logistic regression between quartiles of inpatient opioid consumption. Results  A total of 437 patients were included: 169 patients underwent VD, and 268 underwent CD. For VD and CD, women in the highest quartile of inpatient opioid consumption were more likely Black compared with the lowest quartile ( p  = 0.006 and p  = 0.004, respectively). No association existed between inpatient opioid use and number of tablets prescribed at discharge for VD or CD (odds ratio [OR] 0.22 [95% confidence interval or CI 0.02–2.17] and OR 1.04 [95% CI 0.85–1.32], respectively). Conclusion  The number of opioid tablets prescribed at discharge had no association with inpatient postpartum consumption after VD or CD.